The rules of the Preliminary Title of the Civil Code on patrimonial matters - Sánchez Lorenzo, Sixto A. (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Article 10 of the Preliminary Title of the Civil Code has survived after fifty years being in force with few modifications. Despite the Europeanization of private international law, many of its rules continue to be totally or partially applicable to the determination of the law applicable to obligations and rights in rem, both in international conflicts of laws and, especially, in domestic conflicts of laws. The present contribution aims to attest to the areas of survival of its rules, their problems of application today and their compatibility with other conventional and European sources.